2017
DOI: 10.1177/1539449217736059
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Orientation to Daily Occupational Performance Approach and Transfer: A Scoping Review

Abstract: Transferring learning from therapy to everyday life skills is a necessary step for successful therapy outcomes, yet rarely addressed and achieved. However, a cognitive approach to skill acquisition, and the Cognitive Orientation to daily Occupational Performance (CO-OP), explicitly identifies transfer as an objective and incorporates elements into the intervention to support transfer. A scoping review was undertaken to explore the nature and extent of the research regarding CO-OP and transfer. An online search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 66 publications
4
20
0
1
Order By: Relevance
“…If the goal was not achieved, the participant and therapist analysed what went wrong and identified a new potential 'plan' and the process was repeated (Dawson et al, 2017). Throughout all sessions, the therapist encouraged generalisation of skills and strategies to the natural environment and transfer to novel skills (Houldin et al, 2018). Each participant addressed at least three goals during their participation in the study.…”
Section: The Craft Interventionmentioning
confidence: 99%
“…If the goal was not achieved, the participant and therapist analysed what went wrong and identified a new potential 'plan' and the process was repeated (Dawson et al, 2017). Throughout all sessions, the therapist encouraged generalisation of skills and strategies to the natural environment and transfer to novel skills (Houldin et al, 2018). Each participant addressed at least three goals during their participation in the study.…”
Section: The Craft Interventionmentioning
confidence: 99%
“…Additionally, they found that detailed intervention plans were rare, and the connection between the goal and the treatment plan was typically vague, with details lacking in how it would be delivered, the frequency of the treatment, and how the client would be involved. The disconnect between the goals and treatment plans threatens the benefits of client-centred goal setting and, further, may limit transfer and generalization to other goals, which is reported to be an important benefit of the CO-OP approach (Houldin et al, 2018). According to the theoretical mechanisms of action of CO-OP, if clients are unaware of why they are doing the intervention, are disengaged in the treatment, or are unsure of how it relates to their goal, it is unlikely that the benefits of client-centred goal setting will occur (Polatajko & Mandich, 2004).…”
Section: Treatment Plansmentioning
confidence: 99%
“…When a functional, occupation-based goal is created collaboratively with a client, it is reasonable to assume the treatment plan that follows will be an intervention for which there is evidence that the occupation-based goal will be met. Client-centred, top-down, task-specific interventions that make the client's goal the direct focus of treatment, such as the CO-OP approach, have demonstrated efficacy in improving a wide range of outcomes (Scammell, Bates, Houldin, & Polatajko, 2016), including transfer to outcomes that are not directly the focus of treatment (Houldin, McEwen, Howell, & Polatajko, 2018). Despite evidence for top-down approaches and increasing evidence that bottom-up approaches do not lead to improvements in function or participation (French et al, 2007;Pollock et al, 2014;Wolf et al, 2016), rehabilitation clinicians continue to focus treatments on impairment reduction (Teasell, Foley, Salter, & Jutai, 2008;Veerbeek et al, 2014).…”
mentioning
confidence: 99%
“…People who have difficulties using experiences from the previous performance of tasks may in fact not be able to use their new skills in new environments and situations [5]. Hence a top-down approach, where the person is involved and cognitively processes the different stages during the performance of an activity, may provide better tools for the transfer of problem-solving skills to new situations [15][16][17][18][19] and thus enhance participation in everyday life. The Cognitive Orientation to daily Occupational Performance Approach (CO-OP Approach TM ) is a top-down, client-centred and performance-based approach which gives the client the opportunity to learn skills by finding his or her own way to solve problems when performing a given task [15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Clients learn to use a "Global Strategy" -"Goal-Plan-Do-Check"which should form the basis for their thinking about how to solve performance problems and how to work towards specific goals. The CO-OP Approach has several objectives: acquiring skills, learning how to use cognitive strategies and using them in new situations and contexts [15][16][17][18][19]. Today there is evidence that the CO-OP is an effective intervention in persons with executive dysfunction for example traumatic brain injury (TBI) [20], and stroke survivors [21,22].…”
Section: Introductionmentioning
confidence: 99%